The incidents of housing policies in the process of nesting the urban space (Buenos Aires, 1870-1999) - Marcús, Juliana (Universidad del Rosario, 2011)
This article describes the housing policies displayed historically in B.A. that affected the processes of configuration and of giving hierarchy to the urban space. Since the process of modernization of B.A., at the end of the XIXth century, housing measures, urbanistic projects and political decisions have influenced the building of the city and the space distribution of their inhabitants: in this way, they have integrated some people and excluded others. No wonder, that, historically, popular sectors have established themselves in the South of the city (and in outskirt villages). These zones have been disregarded by the state, which has invested less in these areas. We will see how the connection between state housing policies and the population redistribution in the city, confirms the persistence of a strong process of urban and residential segregation that tends to expel the inhabitants of popular sectors and to attract the ones of the middle-class and high class sectors.